A new probability model for estimation of child mortality for fixed parity - Maheshwari, Sonam; Singh, Brijesh; Gupta, Puneet (International Journal of Health, 2015)
In demography, child mortality is useful as a sensitive index of a nation’s health conditions and as guided for the structuring of public health schemes. In the present study, we proposed a probability model for the number of child loss among females for a fixed parity. The application of the model proposed in the paper is illustrated through its application to the data from Madhya Pradesh from National Family Health Survey-III (NFHS-III). Finally, we show that proposed model is better fitted than the Beta-Binomial model for the data.